Stream-Riparian Linkages : Searching for Patterns in Invertebrate Community Structure - Devoe, Aaron; Gaffney, Laura; Weirich, Joseph (My University, 2012)
The riparian zone is the terrestrial habitat bordering a stream. Both aquatic and terrestrial invertebrates are found in riparian food webs and each habitat influences the other and comprise the stream ecosystem (Baxter et al., 2005). Riparian zones are excellent indicators of human impact on stream ecosystems. The objective of this study was to examine emergent aquatic and terrestrial invertebrates to document trends in the abundance and distribution of riparian invertebrates in relation to a stream logjam in Beaver Creek, a sandy-bottomed stream near Fall Creek, WI.
Color poster with text, photographs, charts, and graphs.
Keywords: Stream ecology--Wisconsin--Eau Claire County; Riparian areas; Invertebrate communities--Effect of water current on; Wilderness areas--Effect of human beings on; Posters